Anaerobic digestion comparison of manure leachate by high-rate anaerobic reactors - Quiroz Arita, Carlos Enrique, author; Sharvelle, Sybil, advisor; Carlson, Kenneth, advisor; Davis, Jessica, committee member (Colorado State University. Libraries, 2013)
A multi-stage anaerobic digester (MSAD) has been developed to obtain high organic leachate from high solids organic waste, thus high-rate anaerobic reactors can be fed by manure leachate, which can be obtained from a leachate bed reactor. Such configuration not only makes feasible the application of high-rate reactors to treat high solids content manure, but also the hydrolysis and the methanogenesis stages can be separated and controlled, individually. However, limited research is available on achieving ideal hydrodynamic conditions, inoculation, and performance of high-rate anaerobic reactors when manure leachate is used as the carbon source. Thus, this research is aimed not only to compare the performance of three different reactor configurations; the Upflow Anaerobic Sludge Blanket (UASB), fixed film, and a hybrid for processing manure leachate as a carbon source, but also to establish design criteria for such reactors including organic loading rates (OLRs) and hydraulic loading rates (HLRs). In the first part of this research, the influence of the hydraulic loading rates (HLR) in high-rate anaerobic reactors was investigated. The upflow anaerobic sludge blanket (UASB) reactor depicted a Morrill dispersion index (MDI) of 1.7, which is measured to evaluate the plug flow conditions of a reactor by approaching a value of 2 or less, at a HLR of 0.296 m3/m2-h. On the other hand, a MDI of 4 was observed when the HLR was increased to 0.829 m3/m2-h. The variation of the HLR had not notable impact MDI of the fixed-film and hybrid reactors; however, short circuits were observed at low HLR. Thus, the most suitable HLRs of such reactors were 10.632 m3/m2-h for the fixed-film reactor and 12.450 m3/m2-h for the hybrid reactor. To evaluate the performance of the UASB, fixed-film, and hybrid reactors to treat manure leachate, this research resulted in development of a method to inoculate such reactors in a single inoculation reactor. The accomplishment of the inoculation was measured by the redox potential, with values below -300 mV after seven days and remained steady until the day 33 with methane percentages in biogas ranging from 45% to 83%. Additionally, plastic media from the inoculation reactor was tested by the biochemical methane potential (BMP) assay, where inoculated organisms were confirmed to produce methane when supplied with glucose as a substrate. In spite that a hybrid anaerobic reactor inoculated with biomass obtained from an UASB reactor, plastic media, and manure leachate was successfully operated at an OLR of 4 kg/m3-d, when transferring the inoculated sludge and media to high-rate reactors, anaerobic digestion was not accomplished. The experiment setup did not support maintenance of anaerobic conditions. In addition, manifolds and open-channel flows were recommended in this research to enhance the reactors configurations. Moreover, results from hydrodynamic studies were applied to provide recomndations for future design parameter, which are included in this thesis.
Keywords: anaerobic digestion; manure leachate; high-rate anaerobic reactors